Comparative analyses of rice husk cellulose fiber and kaolin particulate reinforced thermoplastic cassava starch biocomposites using the solution casting technique - Agyei-Tuffour, B.; Asante, J.T.; Nyankson, E.; Dodoo-Arhin, D.; Oteng-Peprah, M.; Azeko, S.T.; Azeko, A.S.; Oyewole, O.K.; Yaya, A. (Wiley, 2021)
he potential of biodegradable packaging materials from thermoplastic cassava starch (TPS) reinforced with rice husk cellulose fibers (RHCF) and kaolin particulates (KP) using the solution casting method has been presented. This involved the blending of TPS and RHCF/KP in a plasticizer of ~4 ml of glycerol and ~45 ml of distilled water at 125°C and stirred at 60 rpm until a gel was formed. The gel was cast into sheets and bone-shaped tensile specimens and allowed to dry for 5 days and characterized. The results show a semicrystalline structure for TPS with an ~36% increase in crystallinity after reinforcement. The O-H bond stretching and the C-H bending bonds due to starch–glycerol reactions were the common functional groups in TPS–RHCF biocomposites, and Si-O-C bonds were characteristics of the silica phase in the kaolin. The water vapor transmission rate (WVTR) reduced to ~34% with KP reinforcements from ~238 g/m.day to 177 g/m.day and to ~74 g/m.day and ~164% for TPS–RHCF. The strength increased with up to 50 wt% kaolin content; ~0.96 MPa yield strength and ~2.60 MPa ultimate tensile strength (UTS) were recorded. For the RHCF reinforced composites, TPS-50 wt% also showed high strengths of ~0.96 MPa yield strength and ~3.50 MPa UTS. The WVTR reduced as content of kaolin was increased. Typically, from 0 to 30 wt% volume fraction of kaolin, the WVTR was reduced by ~34% to 177 g/m.day for TPS–kaolin and by ~164% to ~74 g/m.day in TPS–RHCF. The as-prepared biocomposites have potential as good packaging materials.
Research Article